The napping house - Wood, Audrey; Wood, Don, 1945- (Orlando, Fla. : Harcourt, 1984)
In this cumulative tale, a wakeful flea atop a number of sleeping creatures causes a commotion, with just one bite.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
3.2.
3.2
K-3
Keywords: Children's stories, American; Fleas -- Fiction; Sleep -- Fiction; Fleas -- Fiction; Sleep -- Fiction